Can Reconstructed Se‐Deficient Line Defects in Monolayer VSe2 Induce Magnetism?. Issue 24 (8th May 2020) - Chua, Rebekah; Yang, Jing; He, Xiaoyue; Yu, Xiaojiang; Yu, Wei; Bussolotti, Fabio; Wong, Ping Kwan Johnny; Loh, Kian Ping; Breese, Mark B. H.; Goh, Kuan Eng Johnson; Huang, Yu Li; Wee, Andrew T. S.
Abstract: There have been several recent conflicting reports on the ferromagnetism of clean monolayer VSe2 . Herein, the controllable formation of 1D defect line patterns in vanadium diselenide (VSe2 ) monolayers initiated by thermal annealing is presented. Using scanning tunneling microscopy and q‐plus atomic force microscopy techniques, the 1D line features are determined to be 8‐member‐ring arrays, formed via a Se deficient reconstruction process. The reconstructed VSe2 monolayer with Se‐deficient line defects displays room‐temperature ferromagnetism under X‐ray magnetic circular dichroism and magnetic force microscopy, consistent with the density functional theory calculations. This study possibly resolves the controversy on whether ferromagnetism is intrinsic in monolayer VSe2, and highlights the importance of controlling and understanding the atomic structures of surface defects in 2D crystals, which could play key roles in the material properties and hence potential device applications. Abstract : One‐dimensional defect line patterns are formed in monolayer VSe2 upon high‐temperature annealing. X‐ray magnetic circular dichroism and magnetic force microscopy confirm that such Se‐deficient reconstructed defects cause the onset of ferromagnetism in pristine VSe2 . This study provides a way to engineer the magnetism via controlling the atomic structures of surface defects in 2D crystals.